Lichen planus pemphigoides presenting preferentially over preexisting scars: A rare instance of isotopic phenomenon - Piyush Kumar; Sushil S Savant; Anupam Das; Shahid Hassan; Panchami Deb Barman (Wolters Kluwer Medknow Publications, 2015)
An 18-year-old girl presented with multiple itchy hyperpigmented papules and plaques, along with tense blisters over the lower limbs and buttocks for last 3 months. These papules, plaques, and bullae were mostly localized to preexisting scars. The histopathological findings from papule and bulla were consistent with lichen planus (LP) and bullous pemphigoid, respectively. Direct immunofluorescence (DIF) of perilesional skin around bulla showed linear deposition of IgG and C3. Considering clinical, histopathological and DIF findings, diagnosis of LP pemphigoides (LPP) was made. The preferential localization of LPP lesions over preexisting scars was a very interesting finding in our case an extremely rare instance of the isotopic phenomenon.